The elimination of stressed induced light leakage for in-plane-switching LCD - Wang, Feifei; Zhan, Hongming; Ji, Lintao; Yang, Tao; Meng, Qingyong; Li, Yajun; Li, Bowen; Zang, Yuansheng; Chen, Junsheng; Huang, Yinhu; Wang, Kaixuan; Lin, Lifeng; et al. (Scientific reports, 2022)
As the mainstream display mode of LCD, IPS is overwhelmingly used in many fields of flat displays. However, due to the stress sensitivity of glass, the stressed light leakage is a bottleneck for achieving perfect dark state performance. The conventional scheme of using a compensation polarizer outside the cell has no effect on this light leakage. Although many studies have been conducted to overcome this limitation, the proposed methods have limited effects. Our research team has proposed a novel light leakage compensation mechanism by introducing a positive A plate that is sandwiched between the glass and the LC layer, therefore the light leakage which is caused by the combined effect of the phase retardations from the stressed glasses and the LC layer can be eliminated. In addition to theoretically analyzing the compensation principles of the novel light leakage compensation mechanism, we also use the developed positive A material to prepare light leakage compensation demos. And then the electric-optical characteristics and light leakage compensation effects of the demos are evaluated. While maintaining excellent optical and electrical characteristics, this technology effectively solves the problem of stressed light leakage of glass-based IPS, improves the dark-state image quality, and breaks the application of IPS in products such as curve products.